Three-dimensional craniofacial surface measurement techniques - Tan, Shuen Chuan; Setan, Halim; Majid, Zulkepli (2005)

(untitled)
Accurate and precise measurement of three-dimensional (3D) surface in terms of linear distance, curve surface distance, area occupied and angles between surfaces have become key criteria particularly in reconstruction of craniofacial appearance where the main purpose is to restore a distorted or damage facial area according to surgeons and patients requirements from aesthetic point of view. This paper describes several techniques used in 3D surface measurement using practical mathematical computation together with the usability requirements descriptions. These techniques are described in terms of its purposes of usage, implementation process and mathematical calculation. We summarized in the end that all the above discussed approaches are practically useful in 3D surface measurement.